Effects of Geometrical Parameters in Gravitational Water Vortex Turbines with Conical Basin - Bajracharya, Tri Ratna; Shakya, Shree Raj; Timilsina, Ashesh Babu; Dhakal, Jhalak; Neupane, Subash; Gautam, Ankit; Sapkota, Anil (Journal of Renewable Energy, 2020)
Gravitational Water Vortex Power Plant (GWVPP) is an appropriate means to convert kinetic energy of water to rotational mechanical energy at the very low head site. This study aims to establish a basic reference for the design of the runner for the Gravitational Water Vortex Turbine (GWVT) with a conical basin. Seven different geometrical parameters have been identified for runner design, and the effect of these parameters on the system efficiency has been studied numerically and experimentally. The effect of these parameters has been studied over the range of speed with torque. The results from performance tests of these runners suggest that runner height is the most significant parameter to be considered in the design of a turbine runner for GWVPP with a conical basin. The results show that the efficiency of GWVT has improved up to 47.85% as obtained from experiments.